Perancangan Sistem Pencatatan Transaksi Berbasis Microsoft Excel Untuk Mendukung Penyusunan Laporan Keuangan Dan Pelaporan Pajak Pada UMKM Bengkel Kasda Motor - rafika; Johandri Iqbal (LP2M Politeknik Jambi, 2026)
This study aims to design a transaction recording system based on Microsoft Excel to support financial statement preparation and tax reporting at UMKM Bengkel Kasda Motor. The research was conducted due to the existing manual recording system that has not been able to produce financial statements in accordance with the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) and has not supported accurate calculation of the 0.5 percent Final Income Tax. The research method used in this study is a descriptive qualitative method with data collection techniques through observation, interviews, and documentation. The results of the study indicate that the Microsoft Excel-based recording system is designed to record daily transactions in a structured and integrated manner and generate financial reports consisting of income statements, statements of financial position, and notes to financial statements in accordance with SAK EMKM. Additionally, the system can assist in calculating and adjusting the reporting of Final Income Tax at a rate of 0.5 percent automatically based on business turnover data. Therefore, the designed system can serve as a practical solution for improving financial recording quality and tax compliance.